G124(P) Junior doctors as quality and safety leads. (25th October 2020) - Yassaee, A; Hodder, T; Alam, M
Abstract : Aims: Improve departmental approach to quality and safety (Q+S) issues, reporting culture and frontline staff's engagement with quality improvement through appointment of junior doctor Q+S leads. Methods: Two junior doctors used the Model for Improvement. Cycle 1: Creating an issues log on the bottom of the handover list, enabling any member of the clinical team to Q+S issues. New items were discussed during handover. Issues included significant events, Datixes, and positive episodes which warranted promotion. Cycle 2: Introducing a weekly, minuted departmental meeting, chaired by a trainee. The meeting ran through the issue log, discussed complex cases, and would highlight opportunities for quality improvement. Cycle 3: Creating an online Greatix portal to encourage staff to highlight good practice, coupled with a monthly newsletter. Cycle 4: Formalising the role across changeover in order to ensure sustainability. This included a formal job description, advertisements to incoming trainees and negotiating protected time for individual(s) to carry out the role. Results: The weekly meetings supported multidisciplinary working and promoted the discussion of quality and safety issues in everyday clinical activities. The role has brought significant benefit the department's functioning and it was felt a good use of resource to offer protected time to an incoming trainee. There was good engagement with the Greatix system with 30 submitted and 3 newsletters produced. As a result of the structured approach in the weekly meetings, other trainees felt empowered to lead on their own quality improvement projects, including work with maternity and pathology services. Due to their knowledge, the Q+S leads would often be asked to represent the department at governance/management meetings and their suggestions have led to projects in other departments. Conclusion: Junior doctors can be effective Q+S advocates and leaders. Senior buy-in is essential for trainees to flourish in this role. Experience or training in leadership and/or QI is beneficial.